Peru : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This Informational Annex highlights Peru's current lending portfolio, which includes 17 active projects with a commitment of USD 1.8 billion and an undisbursed balance of USD 1.4 billion. The areas covered by the existing portfolio are economic policy, the environment, social protection, transportation infrastructure, and water resources, among others. Examples of projects include Basic Education, Higher Education, Regional Transport, Lima Optimization of Water Systems, and the Second Rural Electrification Project. The World Bank has an extensive program of analytical and advisory activities for fiscal year 2013/14, including both economic and sector work and nonlending technical assistance. The economic and sector work covers areas such as public expenditure, fiscal incidence, infrastructure, social sectors, climate change, and housing and municipal financing.